Compatibility of Learning Competency Achievement Indicators In Electronic School Book (ESB) Indonesian High School with Critical Thinking Aspects - Imam Safi’i; Ade Hikmat; Ade Eka Anggraini; Sobri Sobri (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The purpose of writing this article is to describe the level of conformity and diversity of development indicators of competency achievement in Indonesian high school BSE with critical thinking aspects emphasized by the Directorate. PSMA Directorate General of Primary and Secondary Education (2017). The method used in this research is content analysis. The research procedure used refers to Huberman and Saldaña (2018). The results showed that in the BSE class X there were 79 items, in class XI as many as 64, and in class XII as many as 55 items. The development of indicators of competency achievement in BSE Indonesian high school in general has been in accordance with critical thinking aspects, but the distribution of each aspect of critical thinking has not been evenly distributed.Abstrak: Tujuan penulisan artikel ini adalah untuk mendeskripsikan tingkat kesesuaian dan keberagaman pengembangan indikator pencapaian kompetensi dalam BSE bahasa Indonesia SMA dengan aspek berpikir kritis yang ditekankan oleh Dit. PSMA Ditjen Pendidikan Dasar dan Menengah (2017). Metode yang digunakan dalam penelitian ini adalah analisis isi. Prosedur penelitian yang digunakan mengacu pada Huberman dan Saldaña (2018). Hasil penelitian menunjukkan, bahwa dalam BSE kelas X terdapat 79 butir, kelas XI sebanyak 64, dan kelas XII sebanyak 55 butir. Pengembangan indikator pencapaian kompetensi pada BSE bahasa Indonesia SMA secara umum telah sesuai dengan aspek berpikir kritis, namun penyebaran tiap aspek berpikir kritis belum merata.